Gasdermin-E Mediated Pyroptosis—A Novel Mechanism Regulating Migration, Invasion and Release of Inflammatory Cytokines in Rheumatoid Arthritis Fibroblast-like Synoviocytes - Wu, Tao; Zhang, Xue-Pei; Zhang, Qian; Zou, Yao-Yao; Ma, Jian-Da; Chen, Le-Feng; Zou, Yao-Wei; Xue, Ji-Meng; Ma, Ruo-Fan; Chen, Zhong; Dai, Lie (Frontiers in Cell and Developmental Biology, 2022)
Synovium fibroblast-like synoviocytes (FLSs) are important participants in the pathogenesis of synovitis and joint destruction in rheumatoid arthritis (RA). Pyroptosis is a pro-inflammatory and cell lytic programmed cell death mechanism mediated by gasdermin (GSDM) family proteins. In this study, we demonstrated the increased expression of GSDME and increased levels of GSDME-mediated pyroptosis in RA synovial tissues. In vitro, stimulation with TNF-α plus hypoxia mimicking the inflammatory and hypoxic environment in RA synovium induced GSDME-mediated pyroptosis in RA-FLSs in combination with the promotion of migration and invasion abilities and the release of inflammatory cytokines (IL-6, IL-8). Moreover, knockdown of GSDME significantly inhibited the proliferation rate, migration/invasion effects and cytokines released through the reduction of GSDME-mediated pyroptosis. The immunohistochemistry results showed that RA patients with high GSDME N-terminal (GSDME-NT) expression, which is the active form of GSDME, showed higher IL-6 expression in both lining and sublining layer of synovium than that in patients with low GSDME-NT expression, osteoarthritis and non-inflammatory orthopedic arthropathies. Our findings revealed a novel mechanism regulating cell proliferation, migration, invasion and inflammatory cytokines release during the process of GSDME mediated pyroptosis in RA.